Comparing the outcome of lateral versus posterior approach for hemi-replacement arthroplasty for neck of femur fracture: A randomised controlled trial - Kafle, Pradeep; Maharjan, Rajiv; Chaudhary, Pashupati; Shah, Amit Bikram; Rijal, Nishchal; Dawadi, Pratikshya (Journal of Kathmandu Medical College, 2022)
Background: Among commonly used approaches, posterior approach (Moore’s) results in better regain of function as it require less muscle dissection, while the lateral approach (Hardinge’s) has a lower risk of dislocation. Objectives: To compare the functional outcome between lateral and posterior approaches for hemiarthroplasty. Methods: This parallel design randomised controlled trial of equivalence (allocation ratio 1:1) was conducted in the department of orthopaedics, BP Koirala Institute of Health Sciences with institutional ethical clearance. Fifty eligible patients of >60 years with isolated traumatic displaced neck of femur fracture, presenting during study period from September 2017 to August 2019, were conveniently recruited and randomly allocated by using computerised Excel random number generation technique to undergo hemi-replacement arthroplasty either by lateral approach (N = 25) or by posterior approach (N = 25) and were evaluated at six weeks, three months, six months, and twelve months. Final statistical analysis was done using SPSS v.20 software among 45 patients because four deceased and one was lost to follow-up. The p-value <0.05 was considered statistically significant. Results: The functional outcome as measured by the Modified Harris Hip score at one year was 83.78 ± 5.89 for lateral approach and 80.40 ± 7.56 for posterior approach group (p = 0.102). The hip pain, mean blood loss, operative time, and prothesis size was similar between the two approaches. Conclusion: The study showed that there was no significant difference between the two approaches for hemireplacement arthroplasty in terms of mean operating time, hip pain, and functional outcomes.